Simsoft: A game for teaching project risk management - Xia, Jianhong (Cecilia); Caulfield, C.; Baccarini, David; Yeo, S. (Murdoch University, 2012)
Risks are part of every project and no amount of planning can anticipate every contingency. Risk management, a major component in any project management education program, is the systematic identification, monitoring and mitigation of risks so that projects have the best chance of success. Risk management education has traditionally been taught in a classroom setting, but this method can be expensive, slow and rigid. Business games—interactive learning environments in which players explore all the components of a complex situation—are a simple and efficacious alternative.